KDM6A facilitates Xist upregulation at the onset of X inactivation - Josephine Lin; Jinli Zhang; Li Ma; He Fang; Rui Ma; Camille Groneck; Galina N. Filippova; Xinxian Deng; Chizuru Kinoshita; Jessica E. Young; Wenxiu Ma; Christine M. Disteche; et al. (Biology of Sex Differences)
Abstract Background X chromosome inactivation (XCI) is a female-specific process in which one X chromosome is silenced to balance X-linked gene expression between the sexes. XCI is initiated in early development by upregulation of the lncRNA Xist on the future inactive X (Xi). A subset of X-linked genes escape silencing and thus have higher expression in females, suggesting female-specific functions. One of these genes is the highly conserved gene Kdm6a, which encodes a histone demethylase that removes methyl groups at H3K27 to facilitate gene expression. KDM6A mutations have been implicated in congenital disorders such as Kabuki Syndrome, as well as in sex differences in development and cancer. Methods Kdm6a was knocked out (KO) using CRISPR/Cas9 gene editing in hybrid female mouse embryonic stem (ES) cells derived either from a 129 × Mus castaneus (cast) cross or a BL6 x cast cross. In one of the lines a transcriptional stop signal inserted in Tsix results in completely skewed X silencing upon differentiation. The effects of both homozygous and heterozygous Kdm6a KO on Xist expression during the onset of XCI were measured by RT-PCR and RNA-FISH. Changes in gene expression and in H3K27me3 enrichment were investigated using allele-specific RNA-seq and Cut&Run, respectively. KDM6A binding to the Xist gene was characterized by Cut&Run. Results We observed impaired upregulation of Xist and reduced coating of the Xi during early stages of differentiation in Kdm6a KO cells, both homozygous and heterozygous, suggesting a threshold effect of KDM6A. This was associated with aberrant overexpression of genes from the Xi after differentiation, indicating loss of X inactivation potency. Consistent with KDM6A having a direct role in Xist regulation, we found that the histone demethylase binds to the Xist promoter and KO cells show an increase in H3K27me3 at Xist, consistent with reduced expression. Conclusions These results reveal a novel female-specific role for the X-linked histone demethylase, KDM6A in the initiation of XCI through histone demethylase-dependent activation of Xist during early differentiation. Plain language summary X chromosome inactivation is a female-specific mechanism that evolved to balance sex-linked gene dosage between females (XX) and males (XY) by silencing one X chromosome in females. X inactivation begins with the upregulation of the long noncoding RNA Xist on the future inactive X chromosome. While most genes become silenced on the inactive X chromosome some genes escape inactivation and thus have higher expression in females compared to males, suggesting that escape genes may have female-specific functions. One such gene encodes the histone demethylase KDM6A which function is to turn on gene expression by removing repressive histone modifications. In this study, we investigated the role of KDM6A in the regulation of Xist expression during the onset of X inactivation. We found that KDM6A binds to the Xist gene to remove repressive histone marks and facilitate its expression in early development. Indeed, depletion of KDM6A prevents upregulation of Xist due to abnormal persistence of repressive histone modifications. In turn, this results in aberrant overexpression of genes from the inactive X chromosome. Our findings point to a novel mechanism of Xist regulation during the initiation of X inactivation, which may lead to new avenues of treatment to alleviate congenital disorders such as Kabuki syndrome and sex-biased immune disorders where X-linked gene dosage is perturbed.